Changes in incidence and epidemiology of antimicrobial resistant pathogens before and during the COVID-19 pandemic in Germany, 2015–2022 - Jonathan H. J. Baum; Achim Dörre; Felix Reichert; Ines Noll; Marcel Feig; Tim Eckmanns; Mirco Sandfort; Sebastian Haller (BMC Microbiology)
Abstract Background Carbapenem-resistant Gram-negative bacteria and methicillin-resistant Staphylococcus aureus (MRSA) are among WHO’s priority pathogens with antimicrobial resistance (AMR). Studies suggest potential impacts of the COVID-19-pandemic on AMR. We described changes in AMR incidence and epidemiology in Germany during the COVID-19-pandemic. Methods We used two independent datasets, statutory surveillance and laboratory-based Antibiotic Resistance Surveillance (ARS). We included statutory notifications of infections/colonisations of carbapenem-resistant Acinetobacter spp., Klebsiella pneumoniae, Escherichia coli (CRA/CRKP/CREC) and invasive MRSA. Using Poisson/negative binomial regression and assuming continued pre-pandemic (2015/2017–2020) trends, we projected hypothetical notifications as if the pandemic had not occurred. We quantified annual changes during the pandemic period (2020–2022) by comparing to observed notifications. Additional models considered inpatient reductions, seasonality, infections only, or resistant isolates from ARS. Results CRA notified cases were reduced by -30% (95%CI -39%|-20%) in 2020, -23% (-36%|-8%) in 2021, but + 32% (+ 6%|+64%) higher in 2022 relative to hypothetical pre-pandemic projections. Changes were − 35%/-31%/+6% for CRKP, -40%/-61%/-48% for CREC and − 33%/-25%/-20% for MRSA. Statutory-models accounting for fewer inpatients, seasonality and infections only showed similar trends, as did ARS-models for resistant isolates and infections. International mobility for CRA, CRKP and CREC decreased in 2020–2021, then increased in 2022. Conclusions We observed significant reductions of AMR notifications and infections during 2020–2021, also when accounting for fewer inpatients. We conclude a genuine reduction of AMR spread occurred during the pandemic. Factors like fewer hospitalisations and reduced international mobility contributed. Rising international mobility may partly explain increases for CRA, CRKP and CREC in 2022. A solid understanding of AMR trends improves infection prevention and control.